COMPARISON OF PHYSICOCHEMICAL CHARACTERISTICS AND AMINO ACID COMPOSITION OF WATER-SOLUBLE TEMPE FLOUR AND COMMERCIAL SOYBEANPROTEIN ISOLATE - Astawan, Made; Cahyani, Ananda Putri; Maulidyanti, Leonita; Wresdiyati, Tuti (JURNAL PANGAN, 2020)
The aim of this research was to compared the physicochemical characteristics and amino acid composition of conventional water-soluble tempe flour (CWSTF), germinated soybean water-soluble tempe flour (GSWSTF) and commercial soy protein isolate (CPI). Water-soluble tempe flour was made from defatted flour and alkali extraction-isoelectric precipitation. The yield of CWSTF, GSWSTF, and CPI were not significantly different (p>0.05). Proximate analysis of CWSTF and GSWSTF showed significantly different from CPI except water content (p<0.05). The essential amino acids in CWSTF and GSWSTF are lysine, leucine, isoleucine, phenylalanine, valine, methionine, and threonine. Analysis of the physical characteristic CWSTF and GSWSTF showed significantly different (p<0.05) with CPI in colors, aw, and bulk density in a lower with CPI.